SEJARAH PEMBANGUNAN MASJID AGUNG PALEMBANG DALAM VIDEO ANIMASI 3 DIMENSI - Rozie Muhammad; Eka Prasetya Adhy Sugara (Gestalt : Jurnal Desain Komunikasi Visual, 2019)
Palembang Grand Mosque is one of the oldest mosques in Palembang. The shape of this historic building has a lot of architectural rich heritage which holds noble values ​​and information important for the development of cultural and scientific understanding, so it needs to be protected, preserved and told its history in order to foster awareness of national identity and national interests, especially for young people. One form of disseminating information is to utilize animated video media. The use of video in the form of 3-dimensional animation can bring up visual images that look more real to stimulate the imagination of the audience so that it can be carried into the atmosphere of a more lively storyline. This research uses the stages of Pre-production which includes research information, determines visual concepts, letter concepts, color concepts and manuscript, the Production stage which includes sketching, modeling, texturing, animating and rendering and then Post-production which includes by providing transitions , video effects, sound effects, dubbing, music, giving text, color grading and ending with the final rendering. The results of this study are a video animation as information media about the history of the construction of the Great Mosque.